IN VITRO MULTIPLICATION OF TWO ECONOMICALLY IMPORTANT AND ENDANGERED MEDICINAL PLANTS - JUSTICIA GENDARUSSA BRUM AND ADENIA HONDALA (GAERTN) DE WILDE - M, Johnson; V.S, Manickam; Sonali, Das; Yasmin, Nikhat; N, Andal (Malaysian Journal of Science, 2004)
A method for the micropropagation of Justicia gendarussa Brurn and Adenia hondala (Gaertn) de Wilde from nodal segments was developed. High percentage of proliferating microshoot cultures were obtained by placing nodal segments on Murashige and Skoog’s medium supplemented with 4.44Ã‚ÂµM BAP, 8.88Ã‚ÂµM, 2.22Ã‚ÂµM, 22.2Ã‚ÂµM and 2.69Ã‚ÂµM NAA respectively (85 %). Individual shoots were excised and transferred onto half strength MS medium for rooting. The half MS medium augmented with 4.92Ã‚ÂµM IBA produced maximum number (8 & 3 respectively) and maximum percentage (80 & 70 respectively) of rooting. The plantlets could be subsequently hardened to green house conditions.